Paper 53: Comparing Graft Choice in Medial Patellofemoral Ligament Reconstruction. Issue 7 (30th July 2022) - Johnson, Emma; Farronato, Dominic; Pezzulo, Joshua; Brutico, Joseph; Dodson, Christopher; Freedman, Kevin; Cohen, Steven; Hammoud, Sommer; Henstenburg, Jeffrey
Objectives: Disruption of the medial patellofemoral ligament (MPFL) may lead to recurrent lateral patellar dislocation and patellofemoral chondral injury. Optimal graft choice for MPFL reconstruction in the surgical treatment of patellar instability is unknown. While autograft remains readily available, easily harvested, and of lower cost, allograft is a viable alternative and portends several benefits over autograft. Autograft may provide superior strength or lower re-tear rate, but allograft has been shown to have similar outcomes with less donor site morbidity in some series. Overall, there is a paucity of research comparing autograft vs allograft in MPFL reconstruction. Prior studies have been limited by small sample sizes, incomplete data, or heterogeneous patient population. The objectives of this study were to compare outcomes scores, return to activity and revision rates between allograft and autograft in MPFL reconstruction. The authors hypothesized that there would be no significant difference in outcomes between those who received an allograft and those who received an autograft in MPFL reconstruction. Methods: Patients who underwent isolated MPFL reconstruction with allograft or autograft at a single institution between 2013-2020 were retrospectively reviewed. Patients with a follow-up of less than 2 years were excluded, along with those who underwent concomitant tibial tubercle osteotomy or trochleoplasty. Patients were contacted to complete functional assessments including the Single Assessment Numeric Evaluation (SANE), Visual Analog Scale for pain (VAS), and International Knee Documentation Committee (IKDC) scores. Patient demographics and complications were also reviewed. Outcomes were compared between those that underwent allograft and autograft MPFL reconstruction Results: Out of the fourty-six patients that were retrospectively reviewed, thirty-one (67.4%) patients underwent allograft reconstruction, while fifteen (32.6%) patients underwent autograft reconstruction. There were no differences between the two groups in age at surgery (25.2 years old in allograft vs 26.3 years old in autograft group, P=0.726), sex ratio (19F/12M in allograft and 9F/6M in autograft, P=1.000), or BMI (27.0 in allograft and 24.8 in autograft, P=0.179). There was a mean follow up duration of 4.57 years in the allograft group and 4.83 years in the autograft group (P=0.672), with an overall response rate of 70.2%. There were no differences between the two groups when assessing subjective pain using SANE (66.7 in allograft vs 74.5 in autograft, P=0.334) or VAS score (35.7 in allograft vs 22.9 in autograft, P=0.110). Further there were no differences in patient outcomes as assessed by IKDC score (68.3 in allograft vs 76.2 in autograft, P=0.247). Patients who received an allograft returned to activity at an average of 5.9 months, while patients who received an autograft returned to activity at an average of 5.2 months (P=0.416). One patient in the allograft group required revision surgery (P=0.246). Conclusions: Both allograft and autograft remain viable options in MPFL reconstruction. There were no significant differences in failure rates, PROs, pain, or time to return to play between allograft and autograft MPFL reconstruction in this series.